THE SURVEY OF STUDENTS’ PHYSICAL CONDITIONS OF TRADITIONAL BOAT RACE EXTRACURICULAR AT SMAN 22 SURABAYA - RICHO HARDIANTO, YANUAR Amos (Jurnal Prestasi Olahraga, 2013)
Extracurricular is an activity programmed by a school. The activities programmed are adapted to the circumstances. The extracurricular of traditional boat race at SMAN 22 Surabaya is a student organization which accommodates the students to develop their achievement of traditional boat race in Surabaya. In rowing, a rower must have certain skills to row with good and proper techniques. To support the achievement, besides the techniques and training, physical condition elements are also needed. Physical conditions in such a sport include muscular strength, muscular endurance, flexibility, and power. The purpose of this study is to determine the physical condition level of the athletes joining traditional boat race extracurricular at SMAN 22 Surabaya. The analysis method used in this research was descriptive quantitative, while the data collection technique was done by testing the flexibility, abdominal muscle endurance, upper body endurance, high jump, and durability. The objectives of this study were 20 students who join traditional boat race extracurricular at SMAN 22 Surabaya. Based on the analysis result, it can be concluded that the level of the physical condition of athletes in traditional boat race extracurricular at SMAN 22 Surabaya was categorized ?adequate? according to the result of the five tests done the test of flexibility, abdominal muscle endurance, upper body endurance, leg muscle explosive power, and endurance. Keywords: Physical Condition, Extracurricular, Traditional Boat Race.